ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MUZAKKI MEMBAYAR ZAKAT PROFESI DI BAZNAS JAWA TIMUR - Hauli, Anita; Anggraeni, Puspitasari Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aimed to analyze the factors influence muzakki paying professional zakat. The research design was qualitative study and the data collection methods used were observation and questionnaire. This study used data sources that come from Muzakki in Submarine Unit of Koarmada II Surabaya. The method of data analysis used was Binomial Logit Regression Analysis which includes overall model fit test, goodness of fit test, and significance test. The results of this study indicated that most (67%) members of Submarine Unit of Koarmada II Surabaya have paid professional zakat. Muslim professional decisions to paid professional zakat were influenced individually by knowledge of professional zakat, satisfaction of muzakki, quality of service institutions, and religiosity. As for the variables that have a significant effect on the decision of muzakki to paid professional zakat were knowledge of zakat, service and religiosity. while satisfaction has not significant effect on the decision of muzakki to paid professional zakat. Therefore, national zakat agency (Baznas) expected to be able to increase information about the importance of paid professional zakat, as one of the efforts in alleviating and reducing the level of social inequality in society.